Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

Seasonal hydrochemical variations of a regulated river in the North China Plain: mechanisms and implications for chemical weathering - Xi Yang; Tao-Tao Ji; Zhi-Yuan Zhang; Rong-Tao Ma; Xiao-Wei Jiang (Journal of Hydrology, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Integrated metabolomic and transcriptomic analyses reveal that pectin metabolism mediates texture divergence in grape berries - Zhi-Meng Gan; Xiao-Yan Ai; Yong Liu; Wei Zhu; Yang Zhang; Hui-Liang Wang; Fu-Rong Wang; Xiao-Dong Hou; Hua-Ping He; Lin-Zhong Gong (Postharvest Biology and Technology, 2026)

Formation, Potential, and Challenges of Marine-Continental Transitional Shale Gas in China - Caineng Zou; Dazhong Dong; Qin Zhang; Weiliang Kong; Wen Liu; Zhenyu Zhao; Zhi Yang; Qun Zhao; Rong Ding; Guangyin Cai; Tianquan Qu; Wanli Gao; et al. (Journal of Earth Science, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

The causal relationship between polycystic ovary syndrome and structural changes in brain: a Mendelian randomization study - Han Yang; Wei Xie; Camilo Alberto Pinzon Galvis; Si Huang; Xu He; Si-yi Yu; Qing You; Fan-rong Liang; Zhi-yong Xiao; Ning Li (Brain Imaging and Behavior, 2026)

Mitigating 2-MIB and odor-producing cyanobacteria in a shallow drinking-water reservoir using sponge‑iron-assisted water-lifting aeration - Fei Zhang; Rong Li; Hao mu; Yuhai Zhuo; Zhi Yang; Tinglin Huang; Nan Li (Journal of Water Process Engineering, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

A CBAM-integrated deep convolutional neural network for weather radar echo correction to overcome terrain occlusion challenge - Hao Wang; Zhihao Liu; Fugui Zhang; Zhi Li; Qiangyu Zeng; Tiantian Yu; Rong Yang (Advances in Space Research, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Overlooked role of soil microbial-derived carbon in promoting neurotoxic methylmercury production - Man Yang; Zhi-Cheng Hu; Hui-Wen Liu; Wen Zhang; Yun-Yun Hao; Qin Liu; Jia-Xuan Meng; Bo Meng; Qiaoyun Huang; Baohua Gu; Yu-Rong Liu (Journal of Hazardous Materials, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Sesquiterpenoids from Achillea setacea Waldst. & Kit. with anti-inflammatory activity by inhibiting the glycolytic pathway - Gui-Min Xue; Jin-Feng Xue; Jiang-Jing Duan; Hui-Ying Yang; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhi-Qiang Zhang; Rao Li; Dong-Rong Zhu; Guo-Sheng Li (Phytochemistry, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Long-term cadmium stress influenced the immune response of Pardosa pseudoannulata by modulating its gut microbiota and hemolymph metabolome - Jinjin Li; Yuan-de Peng; Rong Zhou; Jie Peng; Qingling She; Xinyi Yang; Juan Wang; Zhi Wang; Qisheng Song (Journal of Environmental Sciences, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Sophormodines A−C, three alkaloids with antiviral activities against the HBV from the seeds of the Tibetan medicine plant Sophora moorcroftiana - Ting-Ting Liu; Meng-Fan Xie; Qing-Qing Yang; Rong-Tao Li; Zhi-Jun Zhang (Phytochemistry, 2025)

The application of nutrients in enhancing drought tolerance of secretohalophyte Atriplex canescens in the desert regions of Northwest China - Jian-jun Kang; Wen-zhi Zhao; Zhi-bin He; Bing Liu; Rong Yang; Hai Zhou; Dong-Mei Zhang (Plant and Soil, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Effects of triclosan on microalgal-bacterial symbiosis system operating in stable phase: Performances and mechanisms - Qiang Chao; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian (Journal of Water Process Engineering, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Contribution of phosphorylation modification by sodium tripolyphosphate to the functional properties of hollow zein nanoparticles - Sheng-qi Rao; Cao-chen Jia; Lin Du; Wei-biao Zhou; Wen-xuan Hu; Yi Jiang; Zhi-rong Wang; Zhen-quan Yang (Food Research International, 2025)

Combination of herbal extracts regulates growth performance, liver and intestinal morphology, antioxidant capacity, and intestinal microbiota in Acrossocheilus fasciatus - Yi Ting Shen; Zhi Li Ding; Xiao Yan Wang; Wen Qi Chen; Rong Xing Xia; Shun Yang; Hui Fei (Aquaculture, 2025)

Long-term cereal-legume intercropping accelerates soil organic carbon loss in subsoil of dryland - Wei Wang; Guang-Rong Chen; Meng-Ying Li; Yinglong Chen; Yang Wang; Hong-Yan Tao; Hui-Zhi Hou; Muhammad Maqsood Ur Rehman; Muhammad Ashraf; Yajie Song; Levis Kavagi; Bao-Zhong Wang; et al. (Resources, Conservation and Recycling, 2024)

Lattice-Engineering modulated band structure facilitates enhanced stability of high-voltage LiCoO2 at 4.6 V - Zhi Zhang; Guang-Xin Wu; Zhou-Liang Tan; He-Zhang Chen; Zhen Yu; Zhen-Rong Yu; Xiao-Bing Huang; Wen-Jie Yang; Ying-De Huang (Chemical Engineering Journal, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

A pooled mycoviral resource in a strain of Rhizoctonia solani are regulators of fungal virulence - Ya Rong Wang; Jia En Su; Zhi Juan Yang; Jie Zhong; Xiao Gang Li; Yi Chen; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Composition of Sphagnum palustre L. extracts using different extraction methods - Zhi Wu; Zheng-Yi Hong; Yang Xu; Dai-Rong Wang; Qing-Bin Han; Ping Liu; Xiao-Rong Liu; Lan-Yue Zhang (Natural Product Research, 2024)

FOXP4-AS1 promotes CD8+ T cell exhaustion and esophageal cancer immune escape through USP10-stabilized PD-L1 - Guo-yi Shen; Yi Zhang; Rong-zhi Huang; Zhi-yong Huang; Le-yi Yang; Ding-zhu Chen; Shao-bin Yang (Immunologic Research, 2024)

Formation mechanism, environmental sensitivity and functional characteristics of succinylated ovalbumin/ε-polylysine electrostatic complexes: The roles of succinylation modification and ε-polylysine combination - Ru-yi Zhang; Hui-min Zhang; Tian-zhu Guan; Zhi-rong Wang; Hua-xiang Li; Lei Yuan; Yan-jun Yang; Sheng-qi Rao (Food Chemistry, 2024)

Capnesterones A and B, new steroids isolated from the soft coral Capnella imbricata - Ting-Yu Cheng; Chia-Jung Yang; Po-Jen Chen; Yu-Li Chen; Bo-Rong Peng; Te-An Kung; Zhi-Hong Wen; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2024)

A new simple index for characterizing the labile heavy metal concentration in soil by diffusive gradients in thin films technique - Yang-xiao-xiao Shi; Hai-rong Xu; Jia Shen; Lin-yu Guo; Jing Yan; Jun Jiang; Zhi-neng Hong; Ren-kou Xu (Environmental Pollution, 2024)

Numerical Investigation on a High-Speed Transom Stern Ship Advancing in Shallow Water - Zhi-Lei Zhao; Bai-Cheng Yang; Zhi-Rong Zhou (Journal of Marine Science and Engineering, 2024)
A high-speed advancing ship will cause significant squats in shallow water, which could increase the risk of grounding. To this end, a program based on the Rankine higher-order boundary element method (HOBEM) is developed to investigate a high-speed displacement ship with a transom stern moving in shallow water. The nonlinear free surface condition is satisfied by adopting an iterative algorithm on the real free surface. The transom condition is considered by implementing a modified transom condition. Computations of wave-making resistance, sinkage and trim in deep water are first performed, and satisfactory agreement is achieved by comparing with the experimental results; the simulations are then extended to the shallow water case. It indicates that the present method can provide a suitable balance of practicability and robustness, which can be considered as an efficient tool for the guidance in ship design stage.

Biodegradation of various grades of polyethylene microplastics by Tenebrio molitor and Tenebrio obscurus larvae: Effects on their physiology - Meng-Qi Ding; Jie Ding; Zhi-Rong Zhang; Mei-Xi Li; Chen-Hao Cui; Ji-Wei Pang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu; Shan-Shan Yang (Journal of Environmental Management, 2024)

Building a stable and robust anti-interference DNA dissipation system by eliminating the accumulation of systemic specified errors - Luojia Wang; Wang Luo; Zhi Weng; Zhongzhong Wang; You Wu; Rong Zhao; Xiaole Han; Xin Liu; Jianhong Zhang; Yujun Yang; Guoming Xie (Analytica Chimica Acta, 2024)

Boron-mediated amelioration of copper toxicity in Citrus sinensis seedlings involved reduced concentrations of copper in leaves and roots and their cell walls rather than increased copper fractions in their cell walls - Huan-Huan Chen; Zhi-Chao Zheng; Dan Hua; Xu-Feng Chen; Zeng-Rong Huang; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2024)

Inflammatory cell death PANoptosis is induced by the anti-cancer curaxin CBL0137 via eliciting the assembly of ZBP1-associated PANoptosome - Ya-Ping Li; Zhi-Ya Zhou; Liang Yan; Yi-Ping You; Hua-Yu Ke; Tao Yuan; Hai-Yan Yang; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Inflammation Research, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

The role of a small molecular dipole moment for efficient non-doped deep blue thermally activated delayed fluorescence emitters - Hong-Ji Tan; Jie-Rong Yu; Zhi-Zhong Lin; Guo-Xi Yang; Zhi-Qiang Long; Ying-Lan Deng; Ze-Lin Zhu; Xian-Kai Chen; Jing-Xin Jian; Qing-Xiao Tong; Chun-Sing Lee (Chemical Engineering Journal, 2024)

A co-located QTL for seven spike architecture-related traits shows promising breeding use potential in common wheat (Triticum aestivum L.) - Jieguang Zhou; Qian Liu; Rong Tian; Huangxin Chen; Jian Wang; Yaoyao Yang; Conghao Zhao; Yanlin Liu; Huaping Tang; Mei Deng; Qiang Xu; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2024)

Investigation on the catalytic performance of magnetic copper ferrite nanoparticles in the catalytic hydroconversion of Hanglaiwan long flame coal - Yong Gao; Wen-Xian Qin; Jin-Jun Bai; Qi-Yang Zhu; Xia-Long Li; Guang-Hui Liu; Xian-Yong Wei; Yu-Hong Kang; Yan-Jun Li; Xiang-Rong Ma; Zhi-Min Zong (Fuel, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Regulation on copper-tolerance in Citrus sinensis seedlings by boron addition: Insights from root exudates, related metabolism, and gene expression - Huan-Huan Chen; Zhi-Chao Zheng; Wen-Shu Chen; Rong-Yu Rao; Xu-Feng Chen; Xin Ye; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2023)

Insights into roles of triclosan in microalgal–bacterial symbiosis system treating wastewater - Cong-Cong Tang; Tian-Yang Wang; Rong Wang; Cristiano Varrone; Zixuan Gan; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Bioresource Technology, 2023)

Fabrication of a novel antioxidant emulsifier through tuning the molecular interaction between soy protein isolates and young apple polyphenols - Zhi Chao Song; Huan Zhang; Peng Fei Niu; Lin Shan Shi; Xue Yan Yang; Yong Hong Meng; Xiao Yu Wang; Tian Gong; Yu Rong Guo (Food Chemistry, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Dauer larva-derived extracellular vesicles extend the life of Caenorhabditis elegans - Jing Ma; Yi-ting Wang; Ling-hui Chen; Bang-ya Yang; Yong-zhu Jiang; Lan-xi Wang; Zhi-qi Chen; Guan-rong Ma; Liao-qiong Fang; Zhi-biao Wang (Biogerontology, 2023)
There is growing evidence that extracellular vesicles (EVs) play a functional role in tissue repair and anti-aging by transferring the contents of donor cells to recipient cells. We hypothesized that Dauer ( C. elegans ), known as “ageless” nematodes, can also secrete extracellular vesicles and influence the lifespan of C. elegans . Here, we isolated EVs of dauer larvae (dauer EVs). Dauer EVs were characterized using transmission electron microscopy, nanoparticle tracking analysis (NTA), and Western blot analysis. Wild-type C. elegans were fed in the presence or absence of dauer EVs and tested for a range of phenotypes, including longevity, mobility and reproductive capacity. Results showed that dauer EVs increased the average lifespan of nematodes by 15.74%, improved mobility, slowed age-related pigmentation as well as body length, and reduced the accumulation of reactive oxygen species and lipids, while not impairing nematode reproductive capacity. These findings suggest that dauer EVs can extend the lifespan of C. elegans as well as the healthy lifespan by reducing ROS accumulation, with potential anti-aging capacity.

Corrigendum to “Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels” [Food Hydrocolloids 139 (2023) 108527] - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Amorphous biomineral-reinforced hydrogels with dramatically enhanced toughness for strain sensing - Jia-hua Liu; Zhengyi Mao; Yuhan Chen; Yunchen Long; Haikun Wu; Junda Shen; Rong Zhang; Oscar W.H. Yeung; Binbin Zhou; Chunyi Zhi; Jian Lu; Yang Yang Li (Chemical Engineering Journal, 2023)

Asymmetry of Salinity Variability in the Tropical Pacific during Interdecadal Pacific Oscillation Phases - Hai Zhi; Zihui Yang; Rong-Hua Zhang; Pengfei Lin; Jifeng Qi; Yu Huang; Meng Dong (Advances in Atmospheric Sciences, 2023)

Molecular Hydrogen Mediates Neurorestorative Effects After Stroke in Diabetic Rats: the TLR4/NF-κB Inflammatory Pathway - Wan-Chao Yang; Ting-ting Li; Qiang Wan; Xin Zhang; Li-Ying Sun; Yu-Rong Zhang; Pei-Chen Lai; Wen-zhi Li (Journal of Neuroimmune Pharmacology, 2023)
Diabetes is an independent risk factor for stroke and amplifies inflammation. Diabetic stroke is associated with a higher risk of death and worse neural function. The identification of effective anti-inflammatory molecules with translational advantages is particularly important to promote perioperative neurorestorative effects. Applying molecular hydrogen, we measured blood glucose levels before and after middle cerebral artery occlusion (MCAO), 48-h cerebral oedema and infarct volumes, as well as 28-day weight, survival and neurological function. We also measured the levels of TLR4, NF-κB p65, phosphorylated NF-κB p65, catecholamines, acetylcholine and inflammatory factors. All measurements comprehensively showed the positive effect and translational advantage of molecular hydrogen on diabetic stroke. Molecular hydrogen improved the weight, survival and long-term neurological function of rats with diabetic stroke and alleviated changes in blood glucose levels before and after middle cerebral artery occlusion (MCAO), but no difference in circadian rhythm was observed. Molecular hydrogen inhibited the phosphorylation of NF-κB and significantly reduced inflammation. Molecular hydrogen mediates neurorestorative effects after stroke in diabetic rats. The effect is independent of circadian rhythms, indicating translational advantages. The molecular mechanism is related to the TLR4/NF-κB pathway and inflammation. Graphical abstract Molecular hydrogen (H 2 ) affects outcomes of ischemic stroke with diabetes mellitus (DM).

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Di-(2-ethylhexyl) phthalate impairs angiogenesis and hematopoiesis via suppressing VEGF signaling in zebrafish - Yang-Xi Hu; Bo-Wen Hu; Ya-Sha Chen; Hong-Min You; Mei-Rong Bai; Lu-Jun Zhang; Zhi-Fu Guo; Chun Liang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Hollow urchin-shaped NCM811 ternary-structure for high rate charge/discharge capability and efficient CO2 adsorption - Fan-Ming Yang; Xiao-Yao Zhou; Xi-Da Li; Zhi-Cheng Yi; Rong Feng; Guo-Wen He (Journal of Environmental Chemical Engineering, 2023)

Pipeline positioning by the surface-to-borehole electromagnetic induction method in a clayey deposit - Guo-Wei Li; Zhi-Ming Ye; Yang Zhou; Guan-Jun He; Guang-Yu Liu; Xin-Rong He (Applied Geophysics, 2023)

Boosting persulfate activation via paper mill sludge-based biochar for efficient degradation of bisphenol A: Inherent multiple active sites - Zhi-Juan Wang; Yang-Qian Lin; Hua-Jing Zhou; Zi-Lian Liu; Rong-Rong Miao; Xi-Meng Xu; Liang He; Qing-Qing Guan (Chemical Engineering Journal, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Urinary phthalate metabolites in pregnant women: occurrences, related factors, and association with maternal hormones - Wei Wu; Zhi-li Ma; Fang Yang; Ping Wu; De-xin Zhang; Rong Zeng; Dan-ling Sun; Liu Cao (Environmental Science and Pollution Research, 2022)

Sediment Resuspension as a Major Contributor to Sinking Particles in the Northwestern South China Sea: Evidence From Observations and Modeling - Lihua Ran; Wentao Ma; Martin G. Wiesner; Yuntao Wang; Jianfang Chen; Lanlan Zhang; Zhi Yang; Jingjing Zhang; Hongliang Li; Jian Ren; Rong Xiang; Erick Fredj (Frontiers in Marine Science, 2022)
The lateral advection of sinking particles is a well-known phenomenon in the South China Sea (SCS) and has a significant impact on the estimation of the efficiency of the biological carbon pump. However, little is known about the sources and pathways of sinking particles. Here, we present benthic and freshwater diatom fluxes and relative abundances collected by a sediment trap deployed at a water depth of 1,000 m and more than 500 m above the seafloor in the northwestern SCS, indicating that laterally transported resuspended sediment accounts for a significant part of the particle flux to the deep sea. A Lagrangian particle tracking model (LPTM) revealed that the resuspended particles likely originated from the neighboring continental slope, approximately 12–145 km to the west of the study site. Sediment trap observations and the LPTM together indicated that the impact of resuspended sediment occurred mainly in the deep water, and especially strong sediment resuspension was related to summer monsoon-induced coastal upwelling. The results suggest that particle resuspension has an important impact on the biological pump as well as on paleoenvironmental reconstructions of the SCS.

Do driving restriction policies effectively alleviate smog pollution in China? - Lan Yi; Zhi-rong Kang; Li Yang; Mohammad Musa; Fei Wang (Environmental Science and Pollution Research, 2022)

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Recombinant L-HN Fusion Antigen Derived from the L and HN Domains of Botulinum Neurotoxin B Stimulates a Protective Antibody Response Against Active Neurotoxin - Zhen Li; Jian-Sheng Lu; Shan Liu; Rong Wang; Qing Xu; Yun-Zhou Yu; Zhi-Xin Yang (Neurotoxicity Research, 2021)

Bi-allelic BRWD1 variants cause male infertility with asthenoteratozoospermia and likely primary ciliary dyskinesia - Ting Guo; Chao-Feng Tu; Dan-Hui Yang; Shui-Zi Ding; Cheng Lei; Rong-Chun Wang; Lv Liu; Xi Kang; Xiao-Qing Shen; Yi-Feng Yang; Zhi-Ping Tan; Yue-Qiu Tan; et al. (Human Genetics, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Phenolic compounds from cultivated Glycyrrhiza uralensis and their PD-1/PD-L1 inhibitory activities - Fang Bao; Hai-Ying Bai; Zheng-Rong Wu; Zhi-Gang Yang (Natural Product Research, 2021)

Knockdown of Arginyl-tRNA Synthetase Attenuates Ischemia-Induced Cerebral Cortex Injury in Rats After Middle Cerebral Artery Occlusion - Yang Liu; Xue-Bin Hu; Li-Zhi Zhang; Zi Wang; Rong Fu (Translational Stroke Research, 2021)
Some researchers have previously shown that RNAi knockdown of arginyl-tRNA synthetase (ArgRS) before or after a hypoxic injury can rescue animals from death, based on the model organism, C. elegans . However, there has been no study on the application of arginyl-tRNA synthetase knockdown in treating mammalian ischemic stroke, and its potential mechanism and effect on ischemic brain damage are still unknown. Here, we focused on the Rars gene, which encodes an arginyl-tRNA synthetase, and examined the effects of Rars knockdown in a permanent middle cerebral artery occlusion model in rats. To achieve this aim, adult male Sprague-Dawley (SD) rats were given right cerebral cortex injections of short hairpin RNA (shRNA) adenovirus (AV) particles to knock down arginyl-tRNA synthetase, and a non-targeting control (NTC) vector or phosphate-buffered solution served as the controls. After 4 days, the rats were exposed to permanent middle cerebral artery occlusion (pMCAO). Then, the right cerebral cortex level of arginyl-tRNA synthetase was examined, and the effects of the Rars knockdown were evaluated by differences in infarction volume, oxidative stress, blood-brain barrier, mitochondrial function, and glucose metabolism at 1 day and 3 days after MCAO. The injection of shRNA adenovirus particles successfully suppressed the expression of arginyl-tRNA synthetase in the cerebral cortex. We observed an improvement in oxidative stress, mitochondrial function, and glucose utilization and a reduction in brain edema compared with the non-targeting control rats with suppressed expression of arginyl-tRNA synthetase mRNA in the ipsilateral ischemic cortex of the brain. Our findings indicate that knockdown of arginyl-tRNA synthetase in the cerebral cortex exerted neuroprotective effects, which were achieved not only by the improvement of oxidative stress and glucose utilization but also by the maintenance of mitochondrial morphological integrity and the preservation of mitochondrial function. Knockdown of ArgRS administration could be a promising approach to protect ischemic stroke.

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Correlation of exosomal microRNA clusters with bone metastasis in non-small cell lung cancer - Xiao-Rong Yang; Can Pi; Ruoying Yu; Xiao-Jun Fan; Xiao-Xiao Peng; Xu-Chao Zhang; Zhi-Hong Chen; Xue Wu; Yang Shao; Yi-Long Wu; Qing Zhou (Clinical & Experimental Metastasis, 2021)
20–40% of lung cancer patients develop bone metastasis (BM) with significantly decreased overall survival. Currently, BM is mainly diagnosed by computerized tomography (CT) scan or magnetic resonance imaging (MRI) when symptom develops. Novel biomarkers with higher prediction value of BM are needed. Plasma-derived exosomal microRNAs had been isolated and sequenced of total 30 non-small cell lung cancer (NSCLC) patients including 16 with bone metastasis and 14 without bone metastasis. Hierarchical clustering based on the total miRNA profile can clearly separate cancer patients and healthy individuals (H), but not patients with (BM +) or without (BM−) BM. Weight Co-expression network of miRNAs (WGCNA) analyses identified three consensus clusters (A, B, C) of highly correlated miRNAs, among which cluster B (144 miRNAs) showed significantly differential expression in lung cancer patients, especially in BM + group. Pathway analysis of cluster B miRNAs revealed enrichment in metabolic pathways that may involve in preconditioning of the metastatic niche. Three differentially expressed miRNAs between BM + and BM− patients within cluster B were identified as miR-574-5p, a suppressor of Wnt/β-catenin pathway, was down-regulated, while miR-328-3p and miR-423-3p, two activators of the same pathway, were up-regulated in BM + patients. Cluster A miRNAs (n = 49) also showed trend of upregulation in BM + patients. Interestingly, pathway analysis indicated that 43 of them are associated with chromosome14, which has been suggested to promote epithelial-mesenchymal transition (EMT) and bone metastasis.

Vallicoccus soli gen. nov., sp. nov., a novel actinobacterium isolated from soil, and description of Vallicoccaceae fam. nov., Motilibacterales ord. nov. - Yu-Zhou Feng; Wei-Xun Chunyu; Rui Liang; Richard L. Hahnke; Peter Schumann; Yu-Rong Zhao; Sheng Gao; Min Yin; Yang Ji; Le Sun; Xiao-Yang Zhi; Shu-Kun Tang (Antonie van Leeuwenhoek, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Blumea hunanensis (Asteraceae: Inuleae), a new species from Hunan, China - Lin-Dong Duan; Yun Lin; Zhi-Rong Yang; Zhen Lu (Kew Bulletin, 2020)

Analysis of nicotine-induced metabolic changes in Blakeslea trispora by GC-MS - Yang Liu; You-ran Shao; Xiang-yu Li; Zhi-ming Wang; Li-rong Yang; Yu-zhou Zhang; Mian-bin Wu; Jian-ming Yao (Journal of Zhejiang University-SCIENCE B, 2020)

Impact of CYP2R1, CYP27A1 and CYP27B1 genetic polymorphisms controlling vitamin D metabolism on susceptibility to hepatitis C virus infection in a high-risk Chinese population - Jing-jing Yang; Hao-zhi Fan; Ting Tian; Meng-ping Wu; Chao-nan Xie; Peng Huang; Rong-bin Yu; Hong-Gang Yi; Yun Zhang; Jie Wang (Archives of Virology, 2019)

Microencapsulated β-carotene preparation using different drying treatments - Xiang-yu Li; Mian-bin Wu; Min Xiao; Shu-huan Lu; Zhi-ming Wang; Jian-ming Yao; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2019)

Evaluation of Whole Blood Trace Element Levels in Chinese Children with Autism Spectrum Disorder - Ling-ling Wu; Shan-shan Mao; Xu Lin; Rong-wang Yang; Zhi-wei Zhu (Biological Trace Element Research, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

Relationship between polymorphisms of the lipid metabolism-related gene PLA2G16 and risk of colorectal cancer in the Chinese population - Xiao-Nv Xie; Jing Yu; Li-Hua Zhang; Zhi-Ying Luo; Dong-Sheng Ouyang; Ling-Jie Zheng; Chun-Yang Wang; Li Yang; Ling Chen; Zhi-Rong Tan (Functional & Integrative Genomics, 2019)

Correction to: Complete chloroplast genome of Firmiana major (Malvaceae), a critically endangered species endemic to southwest China - Ji‑Dong Ya; Zhi‑Xiang Yu; Yong-Qiong Yang; Shu‑Dong Zhang; Zhi‑Rong Zhang; Jie Cai; Jun‑Bo Yang; Wen‑Bin Yu (Conservation Genetics Resources, 2018)

Complete chloroplast genome of Firmiana major (Malvaceae), a critically endangered species endemic to southwest China - Ji-Dong Ya; Zhi-Xiang Yu; Yan-Qiong Yang; Shu-Dong Zhang; Zhi-Rong Zhang; Jie Cai; Jun-Bo Yang; Wen-Bin Yu (Conservation Genetics Resources, 2018)

Elatostema brachyodontum subsp. lengshuiheensis (Urticaceae), a new subspecies from Guizhou, China - Yun Lin; Ming-Tai An; Zhi-Rong Yang; Yan-Qiang Dai; Deng-Li Yu (Kew Bulletin, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Selective and novel cyclin-dependent kinases 4 inhibitor: synthesis and biological evaluation - Qingxiang Guo; Yongtao Li; Chao Zhang; Zhi Huang; Xin Wang; Yongwei Nie; Yao Li; Yanhua Liu; Shengyong Yang; Rong Xiang; Yan Fan (Medicinal Chemistry Research, 2018)

Erratum to: Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Dual-Labeled Time-Resolved Immunofluorometric Assay for the Simultaneous Quantitative Detection of Hepatitis B Virus Antigens in Human Serum - Rong-Liang Liang; Yun-Sen Yang; Jian-Wei Zhou; Tian-Cai Liu; Xu-Ping Xu; Qian-Ni Liang; Zhen-Hua Chen; Zhi-Ning Dong; Ying-Song Wu (Journal of Fluorescence, 2017)

Trichoderma harzianum-induced resistance against Fusarium oxysporum involves regulation of nuclear DNA content, cell viability and cell cycle-related genes expression in cucumber roots - Shuang-Chen Chen; Hong-Jiao Zhao; Zhong-Hong Wang; Cai-Xia Zheng; Pu-Yan Zhao; Zhi-Hua Guan; Hai-Yang Qin; Ai-Rong Liu; Xiao-Min Lin; Golam-Jalal Ahammed (European Journal of Plant Pathology, 2017)

Responses of soil inhabiting nitrogen-cycling microbial communities to wetland degradation on the Zoige Plateau, China - Li-sha Wu; Yuan-yang Nie; Zhi-rong Yang; Jie Zhang (Journal of Mountain Science, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Zinc binds to and directly inhibits protein phosphatase 2A in vitro - Yan Xiong; Dan-Ju Luo; Xiu-Lian Wang; Mei Qiu; Yang Yang; Xiong Yan; Jian-Zhi Wang; Qi-Fa Ye; Rong Liu (Neuroscience Bulletin, 2015)

Isolation and characterization of 18 microsatellites for Aconitum vilmorinianum Kom. (Ranunculaceae) using next-generation sequencing technology - Jun He; Zhi-Rong Zhang; Jun-Bo Yang; Hong Wang; Jing Meng (Conservation Genetics Resources, 2015)

Soil cellulase activity and fungal community responses to wetland degradation in the Zoige Plateau, China - Li-sha Wu; Su Feng; Yuan-yang Nie; Jian-hong Zhou; Zhi-rong Yang; Jie Zhang (Journal of Mountain Science, 2015)

Removal of antibiotics and antibiotic resistance genes in rural wastewater by an integrated constructed wetland - Jun Chen; You-Sheng Liu; Hao-Chang Su; Guang-Guo Ying; Feng Liu; Shuang-Shuang Liu; Liang-Ying He; Zhi-Feng Chen; Yong-Qiang Yang; Fan-Rong Chen (Environmental Science and Pollution Research, 2015)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)

Characterization of the biological properties and complete genome sequence analysis of a cattle-derived rabies virus isolate from the Guangxi province of southern China - Hai-Bo Tang; Zhuan-Ling Lu; Yi-Zhi Zhong; Xiao-Xia He; Tao-Zhen Zhong; Yan Pan; Xian-Kai Wei; Yang Luo; Su-Huan Liao; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Expression of TGF-β1, SNAI1 and MMP-9 is associated with lymph node metastasis in papillary thyroid carcinoma - Ni Wang; Rong Jiang; Jun-Yan Yang; Cui Tang; Lei Yang; Man Xu; Qi-Feng Jiang; Zhi-Min Liu (Journal of Molecular Histology, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Effect of sand-stabilizing shrubs on soil respiration in a temperate desert - Zhi-Shan Zhang; Xin-Rong Li; Robert S. Nowak; Pan Wu; Yan-Hong Gao; Yang Zhao; Lei Huang; Yi-Gang Hu; Rong-Liang Jia (Plant and Soil, 2013)

Expression of yeast acyl-CoA-∆9 desaturase leads to accumulation of unusual monounsaturated fatty acids in soybean seeds - Jin-Ai Xue; Xue Mao; Zhi-Rong Yang; Yong-Mei Wu; Xiao-Yun Jia; Li Zhang; Ai-Qin Yue; Ji-Ping Wang; Run-Zhi Li (Biotechnology Letters, 2013)

The Implantable and Biodegradable PHBHHx 3D Scaffolds Loaded with Protein-Phospholipid Complex for Sustained Delivery of Proteins - Qiang Peng; Yong-Jie Yang; Ting Zhang; Cheng-Yu Wu; Qin Yang; Xun Sun; Tao Gong; Ling Zhang; Zhi-Rong Zhang (Pharmaceutical Research, 2013)

Polymorphisms of UGT1A9 and UGT2B7 influence the pharmacokinetics of mycophenolic acid after a single oral dose in healthy Chinese volunteers - Dong Guo; Liang-Fang Pang; Yang Han; Hong Yang; Guo Wang; Zhi-rong Tan; Wei Zhang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Biomass accumulation and partitioning, photosynthesis, and photosynthetic induction in field-grown maize (Zea mays L.) under low- and high-nitrogen conditions - Jun-Wen Chen; Zhi-Qing Yang; Ping Zhou; Mei-Rong Hai; Tian-Xiang Tang; Yan-Li Liang; Tong-Xin An (Acta Physiologiae Plantarum, 2013)

Structural determination of two new triterpenoid saponins acylated with monoterpenic acid from Gymnocladus chinensis Baill. - Wen Qi; Dan Yuan; Lian-Mei Yang; Ke-Hui Xie; Tian-Zhi Cai; Rong Yang; Hong-Zheng Fu (Natural Product Research, 2012)

Synthesis of aspirin eugenol ester and its biological activity - Jian-yong Li; Yuan-guang Yu; Qi-wen Wang; Ji-yu Zhang; Ya-jun Yang; Bing Li; Xu-zheng Zhou; Jian-rong Niu; Xiao-juan Wei; Xi-wang Liu; Zhi-qi Liu (Medicinal Chemistry Research, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Molecular characterization of a wheat -Thinopyrum ponticum partial amphiploid and its derived substitution line for resistance to stripe rust - Li-Jun Hu; Guang-Rong Li; Zi-Xian Zeng; Zhi-Jian Chang; Cheng Liu; Zu-Jun Yang (Journal of Applied Genetics, 2011)

Establishment of a transgene expression system for the marine microalga Schizochytrium by 18S rDNA-targeted homologous recombination - Ru-Bin Cheng; Xiang-Zhi Lin; Zhao-Kai Wang; Shan-Jun Yang; Hui Rong; Yong Ma (World Journal of Microbiology and Biotechnology, 2011)

PTEN status is related to cell proliferation and self-renewal independent of CD133 phenotype in the glioma-initiating cells - Ru-Bin Cheng; Rui-Juan Ma; Zhao-Kai Wang; Shan-Jun Yang; Xiang-Zhi Lin; Hui Rong; Yong Ma (Molecular and Cellular Biochemistry, 2011)

Kinetic analysis of γ-glutamyltransferase reaction process for measuring activity via an integration strategy at low concentrations of γ-glutamyl p-nitroaniline - Zhi-rong Li; Yin Liu; Xiao-lan Yang; Jun Pu; Bei-zhong Liu; Yong-hua Yuan; Yan-ling Xie; Fei Liao (Journal of Zhejiang University-SCIENCE B, 2011)

Molecular cytogenetic identification of a new wheat-Thinopyrum substitution line with stripe rust resistance - Li-Jun Hu; Guang-Rong Li; Zi-Xian Zeng; Zhi-Jian Chang; Cheng Liu; Jian-Ping Zhou; Zu-Jun Yang (Euphytica, 2011)

Effects of erythromycin on voriconazole pharmacokinetics and association with CYP2C19 polymorphism - Hui-Yan Shi; Jin Yan; Wen-Hui Zhu; Guo-Ping Yang; Zhi-Rong Tan; Wei-Hua Wu; Gan Zhou; Xiao-Ping Chen; Dong-Sheng Ouyang (European Journal of Clinical Pharmacology, 2010)

Mitochondrial development and the influence of its dysfunction during rat adipocyte differentiation - Rong-hua Lu; Hong Ji; Zhi-guang Chang; Shang-shun Su; Gong-she Yang (Molecular Biology Reports, 2010)

Association of TNFAIP3 polymorphism with rheumatic heart disease in Chinese Han population - Rong Hua; Ji-bin Xu; Jiu-cun Wang; Li Zhu; bing Li; Yang Liu; Sheng-dong Huang; Li Jin; Zhi-yun Xu; Xiao-feng Wang (Immunogenetics, 2009)

An investigation of hormesis of trichloroethylene in L-02 liver cells by differential proteomic analysis - Hai-Yan Huang; Jian-Jun Liu; Ren-Rong Xi; Xiu-Mei Xing; Jian-Hui Yuan; Lin-Qing Yang; Gong-Hua Tao; Chun-Mei Gong; Zhi-Xiong Zhuang (Molecular Biology Reports, 2009)

Validation of eight names of Chinese taxa in Ranunculaceae, Rosaceae and Scrophulariaceae - Qi Lin; Miao Sun; Qian Sun; Shu-Qing Bei; Hong-Li Li; Zhi-Rong Yang (Kew Bulletin, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Effect of silymarin on the pharmacokinetics of losartan and its active metabolite E-3174 in healthy Chinese volunteers - Yang Han; Dong Guo; Yao Chen; Yu Chen; Zhi-Rong Tan; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Effect of the untranslated region and signal peptide sequence of the insecticidal gene from Pseudomonas pseudoalcaligenes on the activity of its expression products in tobacco - Min Huang; Da-Xu Li; Wen-Liang Xiang; Hao Chen; Jian-Hua Guo; Jian Zhao; Jie Zhang; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2009)

Occurrence of Fumonisin B1 in Corn from the Main Corn-Producing Areas of China - Hui-Zhi Gong; Rong Ji; Yan-Xi Li; Hong-Yu Zhang; Bing Li; Yue Zhao; Lin Sun; Fei Yu; Jun Yang (Mycopathologia, 2009)

Development of the male reproductive structures in Taxus yunnanensis - Bing-Yi Wang; Jian-Rong Su; Danilo D. Fernando; Zong-Hui Yang; Zhi-Jun Zhang; Xiao-Ming Chen; Yan-Ping Zhang (Plant Systematics and Evolution, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Expression, purification and characterization of a phyA m -phyCs fusion phytase - Li-kou Zou; Hong-ning Wang; Xin Pan; Guo-bao Tian; Zi-wen Xie; Qi Wu; Hui Chen; Tao Xie; Zhi-rong Yang (Journal of Zhejiang University-SCIENCE B, 2008)

Effect of siRNA on HSV-1 plaque formation and relative expression levels of UL39 mRNA - Ren Zhe; Zhang Mei-Ying; Kaio Kitazato; Nobuyuki Kobayash; Zhu Qin-Chang; Zhang Pei-Zhuo; Yang Zhi-Rong; Wang Yi-Fei (Archives of Virology, 2008)

Identification and characterization of ten polymorphic microsatellite loci in the red panda Ailurus fulgens - Liang Zhang; Xu Liang; Zhihe Zhang; Fujun Shen; Wenping Zhang; Kun Wei; Zhi Yang; Rong Hou; Bisong Yue; Hiroshi Kamata; Ken Okabayashi; Shigeo Ohba; et al. (Conservation Genetics, 2008)

Resistin does not down-regulate the transcription of insulin receptor promoter - Xiao-zhi Qiao; Xian-feng Wang; Zhe-rong Xu; Yun-mei Yang (Journal of Zhejiang University-SCIENCE B, 2008)

Polymorphisms in intron 1 of the porcinePOU1F1 gene - Cheng-Yi Song; Bo Gao; Shang-Hui Teng; Xiao-Yang Wang; Fei Xie; Guo-hong Chen; Zhi-Yue Wang; Rong-bin Jing; Jiu-De Mao (Journal of Applied Genetics, 2007)

Development and evaluation of immunoassay for zeranol in bovine urine - Yuan Liu; Cun-zhen Zhang; Xiang-yang Yu; Zhi-yong Zhang; Xiao Zhang; Rong-rong Liu; Xian-jin Liu; Zhen-ming Gong (Journal of Zhejiang University-SCIENCE B, 2007)

Relationship between resistin level in serum and acute coronary syndrome or stable angina pectoris - Xiao-zhi Qiao; Yun-mei Yang; Zhe-rong Xu; Li-ai Yang (Journal of Zhejiang University-SCIENCE B, 2007)

Use of a novel multiplex probe array for rapid identification of Mycobacterium species from clinical isolates - Shu-Lin Zhang; Jian-Guo Shen; Gwan-Han Shen; Zhan-Qiang Sun; Ping-Hui Xu; Yi-Li Peng; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Characterization of a partial amphiploid between Triticum aestivum cv. Chinese Spring and Thinopyrum intermedium ssp. trichophorum - Yang Zu-Jun; Li Guang-Rong; Chang Zhi-Jian; Zhou Jian-Ping; Ren Zheng-Long (Euphytica, 2006)

Evaluation of Aegilops tauschii Cosson for preharvest sprouting tolerance - Liu Deng-Cai; Lan Xiu-Jin; Wang Zhi-Rong; Zheng You-Liang; Zhou Yong-Hong; Yang Jun-Liang; Yen Chi (Genetic Resources and Crop Evolution, 1998)